Injectable and Sprayable Thermoresponsive Hydrogel with Fouling‐Resistance as an Effective Barrier to Prevent Postoperative Cardiac Adhesions - Kun Shi; Tao Li; Xulin Hu; Wen Chen; Yan Yu; Zhongwu Bei; Liping Yuan; Qi Tong; Jiafeng Liu; Qiang Fan; Yongjun Qian; Zhiyong Qian (Advanced Science)
Abstract Postoperative adhesions are inevitable consequences of surgery, resulting in various complications. The risk increases, particularly in cardiac surgery, where reoperations or staged operations are in high demand. The presence of cardiac adhesions severely complicates resternotomy procedures, which may increase the risk of re‐traumatizing, bleeding, operation time extension, and even mortality. Here, a biodegradable thermo‐sensitive fouling‐resistant hydrogel based on poly(D,L‐lactide)/poly(ethylene glycol) (PLEL) micelles is developed, exhibiting high compatibility with both thoracotomies and minimally invasive interventions. By combining the advantages of liquid and film barriers, this hydrogel can completely cover irregular wounds after injecting or spraying and fully avoid direct contact with injuries between adjacent wound surfaces during the critical course of adhesion formation. In both the primary cardiac adhesion model and the severe repeated‐injury cardiac adhesion model, the PLEL hydrogel is more effective than commercially available products (including Interceed film and sodium hyaluronate hydrogel) in significantly reducing the incidence and severity of adhesions, without causing any cardiac dysfunction or organ damage. The powerful anti‐adhesion effect of PLEL hydrogel is closely related to its ability to inhibit the inflammatory response and balance the fibrinolysis system. This injectable and sprayable antifouling thermosensitive hydrogel represents a promising clinical solution for the prevention of postoperative and recurrent cardiac adhesion.